Interrelationship between integrated curriculum and thematic approach from ECDE to Grade Three (Scholars' Journal, 2020)
This article attempts to provide the concept of Basic Level Education from early childhood to grade three and overview integrated curriculum and thematic approaches at this level. The main purpose of the study is to clarify the concept of integrated curriculum and the theme based approach. The data was collected from semi structured interview and focus group discussion using non-probability purposive sampling. As amended Education Act, from early childhood education up to Grade three is considered Basic Level and the children play the vibrant role to shape the rest of the human life. So integrated curriculum has been proposed for Basic Level education from class one to three in Nepal. On the basis of integrated curriculum, the thematic approach can be applied to deliver this curriculum. The core subjects like Maths and languages both Nepali and English can be taught separately but rest of the subject matters have been integrated in recent curriculum under 11 themes. This paper has been described from constructivist worldview. It contributes the significance and relevancy of thematic teaching approach from ECDE to grade three at Basic Level Education to implement the integrated curriculum. An integrated curriculum is a well-organized and managed of various subjects within a single theme which enhances the students learning achievement through various activities. The curriculum which has been blended within theme-based approach would provide more exposure and learning experiences to the learners to achieve the life skills.